One way to do this would simply be to: cube both numerator and denominator. Therefore when you take the cube root of each you will have this answer.

For example: `(root(3)(x^3))/(root(3)(y^3)) = x/y`

Therefore: 3a^2 all cubed would be equivalent to:

`(3a^2)^3= 3^3*a^6=27a^6`

Next: 4b^3 all cubed would be equivalent...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

One way to do this would simply be to: cube both numerator and denominator. Therefore when you take the cube root of each you will have this answer.

For example: `(root(3)(x^3))/(root(3)(y^3)) = x/y`

Therefore: 3a^2 all cubed would be equivalent to:

`(3a^2)^3= 3^3*a^6=27a^6`

Next: 4b^3 all cubed would be equivalent to:

`(4b^3)^3=4^3*b^9=64b^9`

Now just write each expression as the cube root in the numerator and denominator respectively as:

`root(3)(27a^6)/root(3)(64b^9)`

` `